Human resource management and organization behavior : selected perspectives - Tziner, Aharon E. (Aldershot, Hampshire, England ; Burlington, VT : Ashgate, 2002)
This book reviews research findings in both Human Resources Management and Organisational Behaviour.
Includes bibliographical references and index.
rua 24/02/15
Loans
Keywords: Personnel management; Organizational behavior; Human resource management